Tortuous Common Carotid Artery: A Report of Four Cases Observed in Cadaveric Dissections - Joe Iwanaga; Koichi Watanabe; Saga Tsuyoshi; Yoko Tabira; Koh-ichi Yamaki (Case Reports in Otolaryngology)
A tortuous common carotid artery poses a high risk of injury during tracheotomy. Preoperative diagnosis is therefore important to avoid serious complications. We found four cases of tortuous common carotid artery during an anatomical dissection course for students. The first case was a 91-year-old woman who had bilateral tortuous common carotid arteries without arteriosclerosis. Case 2 was a 78-year-old woman who had bilateral tortuous common carotid arteries without arteriosclerosis. Case 3 was an 86-year-old woman who died from bladder cancer and who also had a right tortuous common carotid artery without arteriosclerosis. Case 4 was an 89-year-old woman who had bilateral tortuous common carotid arteries and a tortuous brachiocephalic artery with severe arteriosclerosis. Case 4 was also examined using computed tomography to evaluate the arteriosclerosis. Computed tomography revealed severe calcification of the vascular wall, which was confirmed in the aortic arch and origins of its branches. In all four cases, the tortuosity was located below the level of the thyroid gland. Based on prior study results indicating that fusion between the carotid sheath and visceral fascia was often evident at the level of the thyroid gland, we speculated that the major region in which tortuosity occurs is at the same level or inferior to the level of the thyroid gland.